2013
DOI: 10.1371/journal.pone.0053882
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Evaluation of Statin Pleiotropy: Statins Selectively and Dose-Dependently Reduce Vascular Inflammation

Abstract: Statins are thought to reduce vascular inflammation through lipid independent mechanisms. Evaluation of such an effect in atherosclerotic disease is complicated by simultaneous effects on lipid metabolism. Abdominal aortic aneurysms (AAA) are part of the atherosclerotic spectrum of diseases. Unlike atherosclerotic occlusive disease, AAA is not lipid driven, thus allowing direct evaluation of putative anti-inflammatory effects. The anti-inflammatory potency of increasing doses (0, 20 or 40 mg/day) simvastatin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 43 publications
(64 reference statements)
3
74
1
1
Order By: Relevance
“…Similarly, it was found that statins dose dependently reduce NFκB-driven inflammation in the aneurysm wall. 28 Lacking clear effects on other inflammatory pathways, VDR activation appears highly selectively influencing NFAT-mediated inflammation. Our observations not necessary exclude an effect of VDR activation on other pathways as reported in experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it was found that statins dose dependently reduce NFκB-driven inflammation in the aneurysm wall. 28 Lacking clear effects on other inflammatory pathways, VDR activation appears highly selectively influencing NFAT-mediated inflammation. Our observations not necessary exclude an effect of VDR activation on other pathways as reported in experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 Relative mRNA expression of selected inflammatory mediators, proteases, cytokines, and cell activation markers (log transcript level relative to GAPDH (GAPDH = 0)) Vitamin D receptor activation and vascular inflammation AJ Nieuwland et al A critical point is whether the observed effects of VDR activation are beneficial in the context of AAA disease or vascular disease in general (atherosclerosis). Although cathepsin K 29 and L 30 have both been implicated in the process of aneurysm formation, 31 an apparent dominant role in AAA progression is challenged by the observation that reductions in cathepsin K and L expression during, respectively, statin 28 and ACE inhibitor therapy 27 are not followed by an effect on aneurysms growth. It is unclear whether and if the effects of VDR activation on T-helper cell content will influence AAA disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of the concept has been previously proven for compounds such as statins and doxycycline. [21,25] In this study we evaluated the potential of ramipril, one of more lipophilic members of the ACE-inhibitor family. This compound was chosen for its preclinical efficacy and its superior tissue penetration [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Double staining for CD68/HLA-DR (human leukocyte antigen DR; clone TAL.1B5, 1:1000 dilution, DakoCytomation) was performed in order to assess macrophage activation. [18][19][20][21] The double-stainings were quantified by counting the number of double positive cells in six representative medium power fields (two photographs for each vascular layer) by two independent blinded observers. There was high inter observer reliability for the CD68-CD163, CD68-iNOS, and CD68-HLADR (a50.916, a50.875, a50.839, respectively).…”
Section: Immunohistochemistrymentioning
confidence: 99%